Identifying Material Attributes for Designing Biodegradable Products - Selim I., Lazarevska A. M., Mladenovska. D., Kandikjan T., Sidorenko S. (My University, 2019)
Nowadays, for a number of applications, biodegradable plastics are perceived as an environmentally friendly and often a more sustainable alternative to the commonly used materials. Having this in perspective, a relevant material selection, which simultaneously is affected by the manufacturing constrains, consumers’ needs, market rules, etc., becomes one of the crucial phases in the process of product development. The process becomes even more complex, when the concept of product life cycle is considered. This paper aims to identify relevant attributes for biodegradable materials by conducting a tailor-made survey among students enrolled in design studies. The unjudgmental and creative thinking, in addition to the benefit of not being affected and inhibited by the standard-based restrictions were the main reasons to select these students as relevant stakeholders for this survey. Therefore, utilizing the Ashby and Johnson (2002) categorization methodology which classifies the material attributes into four groups (general, technical, environmental and aesthetical), the students are inspired to propose additional ones, based on their preferences. Further, preferences-based weighting among the complete set of attributes is performed by utilizing the multi-criteria analysis (MCA), and the obtained weights are used as guidance for overall ranking of the attributes’ set. The results of this survey are a sound base towards improving the material selection process influenced both by the designer and the manufacturer perspective.
Keywords: biodegradable materials, attributes, design, multi-criteria analysis